Failure to respond to the patient's coaching: a case study of premature termination in psychodynamic psychotherapy. Issue 4 (2nd October 2022) - Kealy, David; McCollum, James; Curtis, John T.; Silberschatz, George; Katie, Aafjes; Luo, Xiaochen
ABSTRACT: One factor that may help avoid treatment failure by premature termination is the therapist's responsiveness to the patient's coaching. Coaching refers to the patient's efforts to inform and guide the therapist about the kinds of therapist behaviors, attitudes, and interventions that would advance the therapy. The case of Barb, from a naturalistic study of time-limited psychotherapy, was examined as a failed treatment due to premature termination. Using a case study approach, descriptive analysis of the therapy process, along with quantitative ratings of coaching and responsiveness, was employed to examine instances of patient coaching with corresponding therapist responsiveness. Analysis indicated that the patient attempted to coach the therapist throughout each session about her plan for treatment and the responses she sought from the therapist. The therapist's responses were only partially aligned––and in some instances not at all aligned––with the patient's coaching. The disparity between the patient's coaching and the therapist's responsiveness was widest in the two sessions immediately prior to termination. This case study indicates that patients may coach therapists in order to avoid treatment failure. Therapists who attend to patient coaching and modify their responsiveness may be better able to sustain treatment and help patients achieve therapeutic goals.